Diagnosing Lingual Airway Obstruction Using Nasopharyngeal Tube in OSAHS: Natural Sleep vs Induced Sleep - Shuhua Li; Chunhai Shi; Dongmei Yu; Wancheng Chen; Dahai Wu (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Objective: The goal of this study was to use the results from nasopharyngeal tube polysomnography (NPT-PSG) to detect glossopharyngeal airway obstruction in patients with obstructive sleep apnea hypopnea syndrome (OSAHS) and to compare the results with those obtained by observing sleep apnea/ hypopnea after nasopharyngeal tube insertion during drug-induced sleep.  Methods: Fifty-three patients with OSAHS underwent NPT-PSG. In addition, during drug-induced sleep before surgical anesthesia, NPT was inserted, and the incidence of sleep apnea/hypopnea was observed. The observed results were compared with the NPT-PSG results, Both NPT-PSG data and observed data during drug-induced sleep were used to determine whether glossopharyngeal airway obstruction was present, and the two results were compared.  Results: Among the 53 patients, NPT-PSG was successfully completed in 50 and unsuccessfully in 3. All 53 patients completed the examination after NPT insertion during induced sleep successfully. The correlation coeffi cients of apnea-hypopnea index (AHI) and lowest oxygen saturation (LaSO2 ) between the results obtained from the two methods were 0.367 and 0.375, respectively, and P values were less than 0.001 in both cases. When using the two methods to detect the presence of glossopharyngeal airway obstruction, the coincidence rate was 80%.  Conclusion: NPT-PSG results are highly consistent with the results obtained after NPT insertion during induced sleep. For patients in whom NPT-PSG fails to be performed or produces uncertain results, the complementary observation after NPT placement during induced sleep can further clarify the condition of glossopharyngeal airway obstruction.